Glass fiber filled polycarbonate material with good chemical resistance and preparation method thereof
By introducing silicon copolymerized PET into glass fiber filled polycarbonate materials, the problem of poor chemical resistance during injection molding is solved, and the high modulus, thermal deformation temperature and toughness of the material are improved, which is suitable for a variety of applications.
Patent Information
- Application Number
- CN202411933252.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-11
AI Technical Summary
The existing glass fiber filled polycarbonate materials have surface problems during injection molding, resulting in poor chemical resistance and high melt viscosity affecting fluidity.
By introducing silicon copolymerization PET, the chemical resistance of glass fiber-filled polycarbonate materials is improved, and the toughness and thermal deformation temperature of the material are improved by combining the semi-crystalline characteristics of PET and the flexibility of the silicone segments.
It significantly improves the chemical resistance of the material, maintains high modulus, thermal deformation temperature and good toughness, is suitable for various practical applications, and has good development and application prospects.
Smart Images

Figure BDA0005210872240000021 
Figure BDA0005210872240000031 
Figure BDA0005210872240000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polycarbonate alloy materials, in particular to a glass fiber filled polycarbonate material with good chemical resistance and a preparation method thereof. Background Art
[0002] Polycarbonate (PC for short) is a high molecular polymer containing carbonate groups in the molecular chain, and the most commonly used is bisphenol A type PC. Because its molecules contain a large number of benzene ring structures, the molecular chain is relatively rigid, not easy to crystallize, and has a high glass transition temperature. The molecular chain structure characteristics of PC determine that it has many excellent properties, such as balanced rigidity and toughness, good creep resistance and dimensional stability, heat resistance, transparency, low water absorption, non-toxicity, excellent dielectric properties, etc., so it is widely used in electronic appliances, automobiles, communications, medical treatment, home appliances and other fields. But on the other hand, PC has a higher melt viscosity, is sensitive to notches, and has poor resistance to organic chemicals and wear resistance.
[0003] Reinforced modified PC, especially glass fiber filled modified PC materials, are widely used in related fields such as automobiles, construction, consumer electronics, lighting, medical treatment and transportation. Due to the high melt viscosity of PC itself, adding a large amount of inorganic fillers, especially glass fiber reinforcement, usually leads to further deterioration of the fluidity of PC, resulting in more surface problems in the subsequent injection molding process, resulting in further deterioration of its chemical resistance.
[0004] Polyethylene terephthalate (PET) is a semi-crystalline material with good chemical stability, mechanical properties and thermal stability. It is an engineering plastic with a wide range of applications. PET resin has a high glass transition temperature, slow crystallization speed, high molding temperature, long molding cycle, large molding shrinkage, poor dimensional stability, and brittle crystallization. Generally, its processability and physical properties are improved by reinforcement, filling, blending and other methods.
[0005] At present, the patent literature on PC and PET composite materials focuses on improving the slow crystallization rate of PET by adding nucleating agents and crystallization accelerators, and improving the comprehensive properties of the alloy by using appropriate volume expansion and toughening technologies. There are no reports on the modification of PC reinforcement system by copolymerization of PET. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention provides a glass fiber filled polycarbonate material with good chemical resistance and a preparation method thereof. The present invention utilizes the introduction of silicon copolymer PET to significantly improve the chemical resistance of the glass fiber filled polycarbonate material, while the composite material can maintain high modulus, high heat deformation temperature and good toughness.
[0007] The present invention also provides a product prepared from the glass fiber filled polycarbonate material with good chemical resistance.
[0008] The present invention adopts the following technical solutions:
[0009] A glass fiber filled polycarbonate material with good chemical resistance mainly comprises polycarbonate, silicon copolymer PET, glass fiber and other additives, wherein the mass percentages of the polycarbonate, silicon copolymer PET and glass fiber are:
[0010] Polycarbonate 60-80%
[0011] Silicone copolymer PET 1-20%
[0012] Glass fiber 10-40%
[0013] In the present invention, the polycarbonate (PC) comprises homopolycarbonate and copolycarbonate having repeating structural carbonate units, and may be a mixture of one or two of aliphatic polycarbonate, alicyclic polycarbonate or aromatic polycarbonate. In the present invention, suitable polycarbonate may be prepared by methods such as interfacial polymerization and melt polymerization. In a specific embodiment, the polycarbonate is a linear homopolymer derived from bisphenol A, i.e., an aromatic polycarbonate containing a bisphenol A structure, as shown in the following formula:
[0014]
[0015] The polycarbonate actually used in the present invention can be various existing commercially available polycarbonate products, for example, bisphenol A polycarbonate purchased from Teijin, Wanhua Chemical and other companies in Japan.
[0016] Preferably, the melt index of the polycarbonate is 4-20 g / 10 min when measured at 300°C and 1.2 kg. More preferably, the melt index is 8-20 g / 10 min when measured at 300°C and 1.2 kg.
[0017] In the present invention, the silicon copolymer PET is a polyethylene terephthalate / siloxane copolymer, which is prepared by reacting an organic silanol as a comonomer with terephthalic acid and its esters, and ethylene glycol, such as methyl silanol, phenyl silanol, vinyl silanol, etc. The polyethylene terephthalate / siloxane copolymer is prepared by a melt polycondensation method, which can be either a batch method or a continuous method. In terms of raw materials, it can be either an ester exchange route or a direct esterification route. If it is necessary to further increase the molecular weight of the polyethylene terephthalate / siloxane copolymer, it can be achieved by methods such as solid phase viscosity enhancement, chain extension viscosity enhancement, etc.
[0018] In the present invention, the polyethylene terephthalate / siloxane copolymer contains a repeating unit structure represented by the following general formula:
[0019]
[0020] wherein R1 and R2 each independently represent a hydrogen atom, a halogen atom, or a C1-C6 alkyl group (such as methyl, ethyl, propyl, isopropyl, etc.), a C1-C6 alkoxy group (such as methoxy, ethoxy, etc.), or a C6-C 12 As a specific preference, R1 and R2 are each independently selected from methyl. R3 and R4 are each independently selected from divalent C 1-30 As a specific preference, R3 and R4 are each independently selected from a divalent C 2-8 Aliphatic group.
[0021] In the present invention, the polyethylene terephthalate / silicone copolymer comprises 1-40 weight percent siloxane units. Further, the polyethylene terephthalate / silicone copolymer may comprise 60-99 weight percent ethylene terephthalate units and 1 to 40 weight percent siloxane units. Within this range, the polyethylene terephthalate-polysiloxane may comprise 75-99 weight percent ethylene terephthalate units and 1-25% (weight percent) siloxane units, more specifically, 85-95 weight percent ethylene terephthalate units and 5-15 weight percent siloxane units.
[0022] Taking the direct esterification method as an example, a method for preparing polyethylene terephthalate / siloxane copolymer comprises the following steps:
[0023] Terephthalic acid, catalyst and ethylene glycol are sequentially added into the reactor, and nitrogen is added to 0.1MPa; the temperature outside the reactor is set to 260°C for heating, and the pressure is kept constant at 0.25MPa, and the esterification reaction is carried out under this condition. After the esterification reaction is completed, organic silicon diol is added under normal pressure, and the temperature in the reactor is raised to 280°C. In the polycondensation reaction stage, the temperature in the reactor is maintained at 280°C, and the pressure in the reactor is below 100Pa, and the polymerization reaction is carried out under this condition. Preferably, the polymerization catalyst (polycondensation catalyst) is preferably one or more compounds containing Sb, Ti, Ge, Sn, and Al. After the polymerization reaction is completed, stop stirring and use nitrogen to eliminate vacuum, and then discharge the material under nitrogen pressure. The characteristic viscosity of the finished product is 0.5-0.7dl / g. The characteristic viscosity of polyethylene terephthalate / siloxane copolymer can be increased to above 0.8 by solid phase viscosity enhancement or adding a chain extender.
[0024] In addition to the above-mentioned components, the disclosed glass fiber filled polycarbonate material optionally contains one or more additive materials, and the other additives include one or more of heat stabilizers, mold release agents, antioxidants, transesterification inhibitors, antistatic agents, and colorants. Further, the other additives include, for example, heat stabilizers, antioxidants (such as antioxidant 1010 and / or antioxidant 168), hydrolysis stabilizers, chain extenders or light stabilizers, UV absorbing additives, plasticizers, flow promoters, lubricants, mold release agents, transesterification inhibitors, antistatic agents, colorants (such as pigments or dyes) or any combination thereof, which can be added according to actual needs. Further, the transesterification inhibitor is an acid phosphate, including, for example, zinc monophosphate, sodium dihydrogen phosphate, potassium hydrogen phosphate, calcium hydrogen phosphate, acid sodium pyrophosphate and mixtures thereof. Further, the weight percentage of the other additives is 0.5-5%. Preferably, the glass fiber filled polycarbonate material with good chemical resistance has a bending strength of more than 6000 MPa, a notched impact strength of more than 80 J / m at room temperature, and a heat deformation temperature of more than 130°C. At the same time, the material has excellent surface chemical resistance after injection molding.
[0025] Preferably, the weight percentage of the silicon copolymer PET is 5-15%.
[0026] Preferably, the weight percentage of the glass fiber is 15-35%.
[0027] A method for preparing a glass fiber filled polycarbonate material with good chemical resistance as described in any of the above technical solutions, wherein polycarbonate, silicon copolymer PET and other additives are premixed uniformly according to a metering ratio, glass fiber is added by side feeding, and melt blending and extrusion granulation are performed by a twin-screw extruder to obtain a glass fiber filled polycarbonate material with good chemical resistance and excellent mechanical properties. The premixing conditions and the extrusion conditions of the twin-screw extruder can adopt the existing technology.
[0028] Preferably, the screw temperature in the twin-screw extruder is controlled between 240-275° C. The extruded pellets are then dried at 90-120° C. for 3-8 hours before injection molding. The premixing can be completed in a high-speed mixer, and the premixing time is generally 3-5 minutes.
[0029] A product made of the above-mentioned glass fiber filled polycarbonate material with good chemical resistance and excellent mechanical properties. The product is selected from mobile phones, personal computers, medical devices, or automotive related applications. Its significant advantages are high modulus, good material toughness, and the product with good chemical resistance can be obtained by the existing injection molding method in the technical field.
[0030] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0031] The present invention utilizes the introduction of silicon copolymer PET, combines the respective advantages of polycarbonate materials and silicon copolymer PET, utilizes the presence of siloxane segments in silicon copolymer PET, increases the flexibility of the molecular chain, and improves the toughness of the material; at the same time, combined with the semi-crystalline characteristics of PET itself, significantly improves the chemical resistance of the glass fiber filled polycarbonate material, and at the same time, the composite material maintains a high modulus, a high heat deformation temperature, and good toughness, can meet various practical needs, and has good development and application prospects. DETAILED DESCRIPTION
[0032] To explain the content of the invention in more detail, the following further describes it in conjunction with specific embodiments.
[0033] Comparative Examples 1-3 and Examples 1-4
[0034] The PC used in the comparative examples and the examples is a commercially available bisphenol A polycarbonate (PC) resin product of Wanhua Chemical, and its MFR at 300° C. and 1.2 kg is 19 g / min (PC-1) and 10 g / min (PC-2), respectively.
[0035] The PET used in the comparative example is Sinopec Yizheng FG600.
[0036] The polyethylene terephthalate / siloxane copolymer is prepared by a conventional method in a reactor by an ester exchange route. There are two types of silicon copolymer PET used in the embodiment, namely PET-S2415 and PET-S2450. Among them, S2415 means that the copolymerization organic silanol molecular structure contains 15 silylmethyl repeating units, and S2450 means that the organic silanol molecular structure contains 50 silylmethyl repeating units. Both PET-S2415 and PET-S2450 copolymers contain 10 weight percent of siloxane units.
[0037] The glass fiber used in the comparative examples and embodiments is ECS13-4.5-534A, produced by Jushi Group Corporation.
[0038] In the comparative examples and the embodiments, the total amount of material is 10 kg, and the remaining components in the comparative examples and the embodiments include antioxidants (antioxidant 1010 and / or antioxidant 168), ester exchange inhibitors, release agents and colorants (carbon black), etc., and the added amounts are all the same as those in the prior art (for example, the weight ratio of antioxidant 1010 and / or antioxidant 168) and colorant (carbon black) in the embodiments and the comparative examples is 1:1:3).
[0039] Weigh PC material, silicon copolymer PET, glass fiber, antioxidant (antioxidant 1010 or / and antioxidant 168), ester exchange inhibitor, release agent and colorant (carbon black) in proportion, and put all raw materials except glass fiber into high-speed mixer for high-speed premixing for 5 minutes. Add the raw material mixture (main feed) and glass fiber (side feed) premixed in the high-speed mixer into the hopper of the twin-screw extruder for melting, mixing, extrusion, cooling, drying and pelletizing. The screw temperature of the twin-screw extruder is controlled between 240-275℃. After that, the extruded pellets are blown and dried at 100℃ for 4 hours before injection molding. The appearance of the injection molded parts is observed and compared, and various mechanical properties tests, heat resistance and chemical resistance tests are carried out at the same time.
[0040] Among them, the mechanical properties and heat resistance tests adopt the following standards:
[0041] Impact performance test: ASTM D256 and ASTMD4812;
[0042] Tensile properties test: ASTM D638;
[0043] Bending performance test: ASTM D790;
[0044] Heat deformation temperature test: ASTMD648;
[0045] For the ESCR (Environmental Stress Crack Resistance, ESCR) chemical resistance test, the test strip is first bent to 1.0% strain on a specific test fixture, and then the pre-tested chemical agent is applied to the high strain area of the test strip, and its surface changes are visually evaluated within 5 minutes. In order to strengthen and quickly feedback the experimental results, acetone, which is more sensitive to polycarbonate, is used in the present invention for test comparison.
[0046] Table 1
[0047]
[0048] For glass fiber filled PC, the appearance comparison between samples is usually evaluated by observing floating fibers (glass fiber exposed). ESCR comparison uses the occurrence of cracks and cracking as the evaluation standard. It can be seen from the test results shown in Table 1 that in the usual 20% glass fiber filled polycarbonate system, the surface floating fiber phenomenon of the sample is serious, the appearance is poor, and the tolerance to acetone is very poor, and cracking occurs (Comparative Example 1). In Comparative Examples 2-3, with the introduction of a certain amount of PET, the appearance and tolerance to acetone of the composite material are improved to a certain extent, but the unnotched impact strength is significantly reduced. In Example 1-2, with the addition of 5wt% of silicon copolymer PET, the flexural modulus and acetone resistance of the composite material system are significantly improved, while the heat deformation temperature, impact strength and appearance are maintained at a good level. In Example 3-4, with the increase in the amount of silicon copolymer PET, the heat deformation temperature and impact strength of the composite material system are slightly reduced, but its flexural modulus, appearance and chemical resistance are all excellent.
Claims
1. A glass fiber filled polycarbonate material with good chemical resistance, characterized in that: Mainly made of the following components in weight percentage: The sum of the components is 100%.
2. The glass fiber filled polycarbonate material with good chemical resistance according to claim 1, characterized in that: The silicon copolymer PET is a polyethylene terephthalate / siloxane copolymer, which is prepared by reacting organic silanol as a comonomer with terephthalic acid and its ester, and ethylene glycol.
3. The glass fiber filled polycarbonate material with good chemical resistance according to claim 1, characterized in that: The silicon copolymer PET is a polyethylene terephthalate / siloxane copolymer, and the polyethylene terephthalate / siloxane copolymer contains 1-40 weight percent of siloxane units.
4. The glass fiber filled polycarbonate material with good chemical resistance according to claim 1, characterized in that: The melt index of the polycarbonate is measured at 300°C and 1.2 kg and is 4-20 g / 10 min.
5. The glass fiber filled polycarbonate material with good chemical resistance according to claim 1, characterized in that: The other additives include one or more of a stabilizer, a release agent, an ester exchange inhibitor, an antistatic agent, and a colorant.
6. The glass fiber filled polycarbonate material with good chemical resistance according to claim 1, characterized in that: The weight percentage of the silicon copolymer PET is 5-15%; the weight percentage of the glass fiber is 15-35%.
7. A method for preparing the glass fiber filled polycarbonate material with good chemical resistance as claimed in any one of claims 1 to 6, characterized in that: According to the metering ratio, polycarbonate, silicon copolymer PET and other additives are premixed uniformly, and glass fiber is added through side feeding. The mixture is melt-blended and extruded into granules through a twin-screw extruder to obtain a glass-fiber-filled polycarbonate material with good chemical resistance and excellent mechanical properties.